Technique To Measure Resultant Load Vector On Shield Supports (b937ef33-c51b-4de4-a956-dc8be749fea8) - Thomas M. Barczak (International Conference on Ground Control in Mining, 1984)
The resultant load vector is the representation of the forces applied to a longwall roof support element by caving strata into a single, quantifiable measure of support resistance. The relatively complex kinematics of the shield support prohibit a determination of support resistance simply by summation of leg forces. A method is being investigated by the Bureau of Nines to determine the resultant load vector by instrumenting supports with pressure transducers and strain gages to measure leg, canopy capsule, and lemnisoate link forces. This concept has been laboratory tested in the Bureau's Nine Roof Simulator. Functional relationships among variables have been assessed, and confidence intervals have been established for prediction of the resultant load vector parameters.